ANALISIS PENGARUH KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS NASABAH: Studi Kasus Pada Sebuah Bank Daerah Di Kota Medan - Anggiat P. Tambunan (Universitas Methodist Indonesia, 2018)
The study aims to determine the effect of trust and satisfaction on customer loyalty. The case study was conducted at a regional bank office in Medan City. The samples of the research were the customers of the bank and convenience sampling was the sampling technique. The results of the analysis indicate that the variables of trust and customer satisfaction have a positive and significant effect on customer loyalty. The bank is encouraged to maintain customer trust and satisfaction so as to increase customer loyalty.